Qualitative Research in I-O Psychology: Maps, Myths, and Moving Forward. Issue 4 (29th December 2016) - Pratt, Michael G.; Bonaccio, Silvia
Abstract : Qualitative methods are gaining prominence in psychology, as well as related fields such as organizational behavior. Yet, we can find little evidence of qualitative research in our top industrial–organizational (I-O) psychology journals. We argue that the lack of research employing qualitative methods is a loss for the field, and we explore the reasons why few scholars adopt this approach. We then explore where this type of research is published and where it is not. Finally, we discuss and debunk several myths that continue to characterize qualitative methods with an eye toward encouraging a greater appreciation and acceptance of this research tradition.